The Anti-Rheumatoid Activity of Niclosamide in Collagen-Induced Arthritis in Rats - Ali AL-GAREEB; Faiq GORIAL; Ahmed MAHMOOD (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate the anti-arthritic effect of orally administered niclosamide (NCL) on collagen-induced arthritis (CIA) in rats. Materials and methods: The study included 35 Sprague Dawley rats (age range, 3 to 4 months; average weight, 100±10 g) of which seven were used as a negative control group (group A) whereas 28, in which arthritis was induced by injection of collagen type II emulsified by incomplete Freund’s adjuvant and which were considered as CIA rats, were randomly divided equally into four groups and treated for 28 days with: normal saline (group B), low-dose NCL (group C), high-dose NCL (group D), and diclofenac sodium (group E). Body weight, arthritis index, ankle swelling, and footpad thickness were monitored before and after treatment in all groups. At the end of the treatment period, serum levels of tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β), and IL-6 were measured together with a collection of articular synovial tissue to evaluate the pathological changes. Results: After four weeks of treatment period, a high dose of orally administered NCL significantly reduced the arthritis index, footpad thickness, and ankle swelling. Significantly decreased serum levels of inflammatory biomarkers including TNF-α, IL-1β, and IL-6 were observed in rats treated with high-dose oral NCL or intramuscular injection of diclofenac sodium, compared with groups B and C. Histopathological examination revealed that a high dose of NCL significantly reduced the infiltration of inflammatory cells, synovial hyperplasia, and bone and cartilage destruction. Conclusion: Niclosamide can effectively decrease the clinical scores, joint swelling, inflammatory markers, and pathological changes in arthritic rats.